The Impact of Authentic Leadership on Work Engagement and Job Satisfaction - Janota, Rui Manuel Gonçalves (Digital Repository of Theses, 2026)
Authentic Leadership emerged as an appealing leadership model based on the employee's self-awareness, relational transparency, internalized moral perspective, and the balanced processing of information. This research evaluated the impact of Authentic Leadership on Work Engagement and Job Satisfaction, among the sales representatives of pharmaceutical companies operating in Portugal, grounded in the framework of the Institutional Theory. This study employed a quantitative, explanatory, cross-sectional research design by using a four-part structured questionnaire, which combined three established instruments, to collect data from 1.415 respondents. The results of this research suggest that Authentic Leadership has a positive impact on both employee Work Engagement and Job Satisfaction, implying that features of this leadership style create a healthy workplace environment. In addition, this positive impact grows with a rise in institutional alignment as Authentic Leadership aligns with, rather than opposes, compliance demands. This research shows that Authentic Leadership behaviors enhance both ethical culture and business outcomes. It further reveals that institutionalized compliance can strengthen authenticity by clarifying values and expectations, shifting compliance from coercive control to strategic empowerment. This study introduces a new concept of “Tempered Authenticity,” revealing that employees can balance candor with contextual sensitivity in regulated environments. The integration of Institutional Theory proposes an ethical performance equilibrium where compliance and performance reinforce each other. Keywords: Authentic Leadership, Organizational Trust, Organizational Commitment, Work Engagement, and Tempered Authenticity.